STUDY OF FISHING GROUND GOMBANG FISHING GEAR IN MESKOM VILLAGE BENGKALIS DISTRICT BENGKALIS REGENCY RIAU PROVINCE - Feby Pandji Syaputra; Alit Hindri Yani; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTOne of the kind  of dominan fishing gear operated by fishermen in the bengkalis strait is gombang.The purpose of this study was determine the fishing ground condition  forgombang based on the environmentalcharacteristics, and  catch composision.This study was conducted inSeptembertoOctober 2017in the Bengkalis Strait Meskom Village Bengkalis District Bengkalis Regency Riau Province, using survey method.The results showed that the fishing ground was located at 01o32'58,6 "NL and 102o01'01,4" EL,can be reached within 10-25 minutes.Characteristics of fishing ground are water temperature24,6-30,5 (̊C),  speed of intermediate current0,25-0,42 (m/s), intermediate nature 26-28,75 (cm), the depth between9,5-12 (m), salinity between26-30 (%0), and pH between 7-8. During the research, captured32 spesieses, the   main catch is shrimp (Mysis sp) and the by-catch are pelagic fish. The number of catches is 515.36 (kg) or 343092 tails. Keywords: Meskom Village, Gombang, Study of Fishing Ground gombang